2011
DOI: 10.1016/j.snb.2011.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Artificial neural network onto eight bit microcontroller for Secchi depth calculation

Abstract: A comprehensive study aimed at evaluating the occurrence, significance of concentrations and spatial distribution of priority pollutants (PPs) along the Comunidad Valenciana coastal waters (Spain) was carried out in order to fulfil the European Water Framework Directive (WFD). Additionally, PPs concentrations were also analysed in the effluent of 28 WWTPs distributed along the studied area, since these infrastructures are usually considered a significant point source of many of these toxic substances.In coasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Actually, this type of development [48] has already been successfully applied using simplified ANNs, [49,50] which are even simpler, computationally less demanding, quick to program, easy to use and very reliable [51]. The goal was to work with a prediction system that is more flexible, adaptive and versatile than the traditional statistical data treatment methods [52,53]. It was particularly interesting considering that the samples were natural fruits that were subject to a wide set of variables that could have generated more or less diversity among them despite belonging to the same species and the same batch (ripeness, acidity, sugar contents, size, time since they were collected, etc.).…”
Section: Methodsmentioning
confidence: 99%
“…Actually, this type of development [48] has already been successfully applied using simplified ANNs, [49,50] which are even simpler, computationally less demanding, quick to program, easy to use and very reliable [51]. The goal was to work with a prediction system that is more flexible, adaptive and versatile than the traditional statistical data treatment methods [52,53]. It was particularly interesting considering that the samples were natural fruits that were subject to a wide set of variables that could have generated more or less diversity among them despite belonging to the same species and the same batch (ripeness, acidity, sugar contents, size, time since they were collected, etc.).…”
Section: Methodsmentioning
confidence: 99%
“…In order to carry out a more precise, flexible, and adaptive prediction model than those traditionally conducted by PLS [35,36], an ANN model was developed. To do so, the software Alyuda Neurointelligence 2.2 © (Alyuda Research Inc., Cupertino, CA, USA) was used.…”
Section: Methodsmentioning
confidence: 99%
“…A commercial ANN software (Alyuda Neurointelligence 2.2 © , Alyuda Research Inc., Los Altos, CA, USA) was used throughout this study in order to create alternative, flexible and more adaptive predictive models to PLS [ 35 , 38 , 39 ]. Multi-layer feed forward neural networks and a single hidden layer ANN structure were selected and on-line back propagation training algorithms were used for fitting the network.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, several trials suggested the selection of logistic-type transfer functions for the output layer neurons and hyperbolic tangent-type functions for the hidden nodes. Random data division was used by Alyuda Neurointelligence 2.2 © in order to select the samples for training (70%), validation (15%) and test (15%) data [ 38 , 39 , 40 ]. In addition, overfitting was avoided by using proportional number of nodes in the network architecture [ 45 ], cross validation and early-stopping in the training phase, so that the difference between training and validation mean square errors was minimal.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation